Phytohormone abscisic acid boosts pentobarbital-induced sleep through activation of GABA-A, PPARβ and PPARγ receptor signaling - MADADZADEH, Mohammad; ABBASNEJAD, Mehdi; MOLLASHAHI, Mahtab; POURRAHIMI, Ali Mohammad; ESMAEILI-MAHANI, Saeed (Arquivos de Neuro-Psiquiatria, 2021)
Background: Sleep disorders induce anxiety and forgetfulness and change habits. The chemical hypnotic drugs currently used have serious side effects and, therefore, people are drawn towards using natural compounds such as plant-based healing agents. Abscisic acid (ABA) is produced in a variety of mammalian tissues and it is involved in many neurophysiological functions. Objective: To investigate the possible effect of ABA on pentobarbital-induced sleep and its possible signaling through GABA-A and PPAR (γ and β) receptors, in male Wistar rats. Methods: The possible effect of ABA (5 and 10 μg/rat, intracerebroventricularly) on sleep onset latency time and duration was evaluated in a V-maze model of sleep. Pentobarbital sodium (40 mg/kg, intraperitoneally) was injected to induce sleep 30 min after administration of ABA. PPARβ (GSK0660, 80 nM/rat), PPARγ (GW9662, 3 nM/rat) or GABA-A receptor (bicuculline, 6 μg/rat) antagonists were given 15 min before ABA injection. Diazepam (2 mg/kg, intraperitoneally) was used as a positive control group. Results: ABA at 5 μg significantly boosted the pentobarbital-induced subhypnotic effects and promoted induction of sleep onset in a manner comparable to diazepam treatment. Furthermore, pretreatment with bicuculline significantly abolished the ABA effects on sleep parameters, while the amplifying effects of ABA on the induction of sleep onset was not significantly affected by PPARβ or PPARγ antagonists. The sleep prolonging effect of ABA was significantly prevented by both PPAR antagonists. Conclusions: The data showed that ABA boosts pentobarbital-induced sleep and that GABA-A, PPARβ and PPARγ receptors are, at least in part, involved in ABA signaling.
Keywords: Abscisic Acid; Sleep; Pentobarbital; PPAR beta; Receptors, GABA-A; Rats